Gender-Based Violence and 2SLGBTQI+ Groups - Cara A. Davidson; Tara Mantler; Kimberley T. Jackson (Societies)
Gender-based violence (GBV) is a pervasive public health issue that affects all Canadians, including Indigenous peoples (First Nations, Inuit, Métis); however, it is well-understood that GBV disproportionately affects certain social groups. An estimated one million Canadians aged 15 and older identify with a sexual orientation other than heterosexual, and approximately 1 in 300 people identify as transgender or non-binary. In Canada, violence rooted in biphobia, homophobia, transphobia, and queerphobia results in disproportionately high levels of GBV experienced by Two-Spirit, lesbian, gay, bisexual, transgender, queer (or questioning), intersex, and other individuals who identify outside of cisgender, heterosexual norms (2SLGBTQI+ people). The health impacts of GBV experienced by people who identify outside of gender and sexuality norms are profound, spanning mental and physical dimensions across the life course. This article employs an anti-oppression queer framework to provide a comprehensive overview of current knowledge and understandings of GBV in Canada concerning 2SLGBTQI+ people, emphasizing (1) the disproportionate risk of GBV faced by 2SLGBTQI+ communities within the context of Canadian social politics; (2) key links between the experiences of GBV among 2SLGBTQI+ people in Canada and associated health disparities; (3) current orientations to GBV policy, practice, and research, with an emphasis on contemporary, inclusive paradigms that shape equity-oriented health and social services; and (4) future directions aimed at eradicating GBV and addressing health inequities among 2SLGBTQI+ people in Canada. While much work remains to be done, the expansion of 2SLGBTQI+ inclusion in GBV prevention within the past five years points to a promising future.